Assessment literacy as a component of the professional competence of a teacher in the conditions of reforming the evaluation system in Kazakhstani schools (Journal of Educational Sciences, 2021)
The realities of modern world have led to reform of educational systems in different countries. Assessment is recognized as main component in determining effectiveness of training. In context of a shift in emphasis from «assessment of learning» to «assessment for learning», problem of developing assessment literacy of practicing teachers and students - future teachers becomes urgent Directions of research: based on analysis of literature on educational assessment, identify approaches to determining teacher’s assessment literacy; to highlight requirements for assessment activity of a teacher and, based on theoretical premises, organize and conduct an empirical study in order to identify significance of this problem in Kazakhstan education and possible ways to solve it. The theoretical research was carried out using a comparative analysis of scientific sources and regulatory documents on problem of educational assessment and a survey of practicing teachers, which formed basis of empirical research. Analysis and systematization of survey results showed that advanced training courses for teachers and courses on criteria-based assessment for university students provide a knowledge component of teacher’s assessment literacy, but problem of improving practical component remains. The solution to this problem is possible through various practices of professional development of teachers, involving theoretical training and independent design of their own assessment activities, taking into account the subject specifics of discipline. Of particular importance in formation of teacher’s assessment literacy is training of future teachers during their studies at university, which should be implemented through formation of deep knowledge in chosen subject area, participation in assessment practices within framework of methodological disciplines and pedagogical practices, interaction with practicing teachers. The scientific and pedagogical significance of study lies in obtaining author’s definition of teacher’s assessment literacy, as well as establishing main directions of its formation and development. Key words: educational assessment, assessment literacy of teachers, formative assessment, summative assessment.